2011
DOI: 10.5483/bmbrep.2011.44.5.306
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in NCX-3 immunoreactivity within the gerbil hippocampus following spontaneous seizures

Abstract: Although NCX-3 is highly expressed in the brain, the distribution of NCX-3 in the epileptic hippocampus is still controversial. Therefore, to assess the distribution and pattern of NCX-3 expression in epileptic hippocampus, we performed a comparative analysis of NCX-3 immunoreactivities in the hippocampus of seizure-resistant (SR) and seizure-sensitive (SS) gerbils. In SR gerbils, NCX-3 immunoreactivity was higher than pre-seizure SS gerbils, particularly in the pavalbumin (PV)-positive interneurons. Three h p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…This finding suggests that downregulation of hippocampal NCX3 is involved in the hyperexcitability of seizure-sensitive gerbils. The different results between the previous and present studies could be explained by the animal models used: Park et al (2011) used the inherited epilepsy model in gerbils, while we used a PTZ-induced kindling model in mice. Since their immunohistochemical study focused on expression of NCX3 in the hippocampus of the gerbils, it is not known whether NCX1 plays a key role in the hyperexcitability of seizure-sensitive gerbils.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…This finding suggests that downregulation of hippocampal NCX3 is involved in the hyperexcitability of seizure-sensitive gerbils. The different results between the previous and present studies could be explained by the animal models used: Park et al (2011) used the inherited epilepsy model in gerbils, while we used a PTZ-induced kindling model in mice. Since their immunohistochemical study focused on expression of NCX3 in the hippocampus of the gerbils, it is not known whether NCX1 plays a key role in the hyperexcitability of seizure-sensitive gerbils.…”
Section: Discussioncontrasting
confidence: 52%
“…We found that hippocampal NCX3 expression, unlike that of NCX1 and NCX2, was not altered by chronic administration of PTZ. In contrast, Park et al (2011) reported that NCX3 may be involved in the pathogenesis of tonic-clonic seizures in Mongolian gerbils, a model of inherited epilepsy. They showed that NCX3 immunoreactivity in seizure-resistant gerbils was higher than in pre-seizure seizuresensitive gerbils, and in the seizure-sensitive gerbil hippocampus NCX3 immunoreactivity after seizure was increased to the level of seizure-resistant gerbils.…”
Section: Discussionmentioning
confidence: 83%
“…(9) and other previous studies (14, 15). Only animals with a consistent stage 4 or 5 seizure score according to the seizure severity rating scale of Loskota et al (34) were included in the present study, and were described as seizure sensitive (SS, n = 10) gerbils.…”
Section: Methodsmentioning
confidence: 97%
“…and perfused transcardially with phosphate-buffered saline (PBS, pH 7.4) followed by 4% paraformaldehyde in 0.1 M PBS. After this, tissue processing and immunohistochemistry processes were performed according to pervious described studies (14, 15). The sections were firstly incubated in mouse anti-ACTH antiserum (diluted 1:400; Peninsula, USA) containing 0.3% Triton X-100 and 2% normal goat serum overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation